Meningkatkan Literasi Budaya : Memahami Budaya Lokal di Sekolah Dasar - Khalimatu Sa’diyah, Melani; Dinie Anggraeni Dewi (Jurnal Multidisiplin Indonesia, 2023)
Indonesia has a diversity of tribes, cultures, languages and beliefs. As a country involved in globalization and progress, Indonesia is impacted by many international partnerships both positively and negatively. As a result, each ethnic group has brought diversity to Indonesia, in line with this there is a need for cultural literacy to interpret the diversity that occurs. This research aims to describe local wisdom in learning through cultural literacy. Local culture from an early age becomes a guide for children's educational development. Education based on local culture must be able to run in harmony with current educational trends, culture is included in the learning process as a tool for teaching cultural values. Teachers are encouraged to use creativity in creating resources that combine local wisdom with materials for elementary school students. Content derived from students' local knowledge can provide context and significance to teaching. Therefore, to implement character education based on local wisdom requires continuous effort and dedication. A learning approach that utilizes the environment as a goal, source and learning instrument is known as "environment-based learning". This can be applied to overcome environmental problems and foster appreciation for nature. Because by getting used to it continuously and continuously, a child will appear.